Catch, effort and bycatch of longline fishery in central Peru - Ayala, Liliana (2014)
The aims of this study is to report some characteristics of fishing trips, effort, catches, fishing areas and bycatch through observations on board and logbooks. 85% of sets were in the first 574 Km of distance from the coast (309 nautical miles). Farthest set was located at 1320 Km (712 nautical miles). A total of 382000 hooks were used to catch Mahi mahi, in 224 sets and 29 fishing trips, 94.6% of catch was Mahi mahi, 2.7% blue shark (Prionace glauca) y 1,3% mako shark (Isurus oxyrinchus). Also, 103790 hooks were used to catch sharks, in 109 sets y 12 trips, 81.9% of catch was blue sharks and 16.8% mako sharks. Catch per Unit of Effort (CPUE) for Mahi mahi shows significative difference among seasons; with a peak from November to January. CPUE for shark shows significative difference among seasons, with peaks in September and October. The Green turtle Chelonia mydas agassizii was the most caugth species and two of three were juveniles. All Loggerhead turtles, Caretta caretta, caught were juveniles. A petrel is reported as bycatch and, probably, mammal bycatch is scarce. Considering the huge effort of this fishery, it is important to monitor it and establish management actions.